1971
DOI: 10.1136/bjo.55.9.591
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of TRIC agent (Chlamydia) in irradiated McCoy cell culture from endemic trachoma in field studies in Iran. Comparison with other laboratory tests for detection of Chlamydia.

Abstract: (I967), has been used to recover laboratory-adapted isolates of TRIC agent from the infected eyes of simians (Gordon and others, I963) and of man (Magruder and others, I963).Studies recently completed in this laboratory on clinical specimens from genital or genitally-related ocular infections in London showed that isolation in irradiated McCoy cells is more sensitive for the detection and isolation of chlamydial agents than cultivation in the yolk sac of embryonated hen's eggs or inclusion-finding in Giemsa-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…McComb and Nichols (1970) showed by a complex cross-absorption technique that antibody in eye secretions faithfully reflected the type of TRIC agent infecting the eye. Studies in our laboratory (Darougar et al, 1971b;Treharne et al, 1971;Treharne et al, 1972;Jones, 1974) have shown, in agreement with the work of others (Wang and Grayston, 1970;Wang and Grayston, 1974), that TRIC agent serotypes A, B, and C are mainly responsible for ocular infection in hyperendemic trachoma areas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…McComb and Nichols (1970) showed by a complex cross-absorption technique that antibody in eye secretions faithfully reflected the type of TRIC agent infecting the eye. Studies in our laboratory (Darougar et al, 1971b;Treharne et al, 1971;Treharne et al, 1972;Jones, 1974) have shown, in agreement with the work of others (Wang and Grayston, 1970;Wang and Grayston, 1974), that TRIC agent serotypes A, B, and C are mainly responsible for ocular infection in hyperendemic trachoma areas.…”
Section: Discussionsupporting
confidence: 90%
“…Methods of ocular examination, assessmenit of the intensity of conjunctival inflammatory disease in trachoma, and methods of collection of specimens for the isolation of C. trachomatis are reported elsewhere (Darougar et al, 1971a;Darougar and Jones, 1971;Darougar et al, 1971b;Dawson et al, 1975). SEROTYPING Isolates from cell culture were inoculated into yolk sacs of developing chick embryos to produce antigen for use in the micro-IF test (Treharne et al, 1973).…”
Section: Conjunctival Specimensmentioning
confidence: 99%
“…Definitive diagnosis of chlamydial infections is usually made by isolation of infectious organisms in cell culture (Darougar et al, 1971) or by direct demonstration of specific antigens in inflammatory exudates using monoclonal antibody staining (Tam et al, 1984). Both methods, although specific and sensitive, need microscopy for evaluation of test results and are therefore time consuming and require a trained specialist.…”
Section: Introductionmentioning
confidence: 99%
“…Received for publication 26 January 1978 COLLECTION AND STORAGE OF SPECIMENS Conjunctival scrapings The conjunctivae of cats were anaesthetised with three to four drops of Jocaine (Darougar et al, 1971b). Conjunctival scrapings were collected using sterile aluminium scrapers, which were flattened at both ends.…”
mentioning
confidence: 99%